96.7k views
1 vote
Please answer the question:

Please answer the question:-example-1
User Codaniel
by
4.6k points

2 Answers

5 votes

Answer:

5

Explanation:


\because {(x + y)}^(2) = {x}^(2) + {y}^(2) + 2xy \\ \therefore \: {(5)}^(2) = {x}^(2) + {y}^(2) + 2 * 10 \\ \therefore \: 25 = {x}^(2) + {y}^(2) + 20 \\ \therefore \: 25 - 20 = {x}^(2) + {y}^(2) \\ \huge \red{ \boxed{ \therefore \: {x}^(2) + {y}^(2) = 5}}

User Pajaja
by
4.9k points
2 votes

Answer:

Option 1

Explanation:

The formula is:


(x+y)^2 = x^2+y^2+2xy

Putting x+y = 5, xy = 10

=> (5)² = x²+y²+2(10)

=> 25 = x²+y²+20

=> x²+y² = 25 - 20

=> x²+y² = 5

User Nateous
by
4.8k points